Higher Education Financing and Income Redistribution - Berthold U. Wigger (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper considers an optimal income tax cum higher educationpolicy.It shows that in the presence of an optimal income tax systemhigher education should be taxed rather than subsidized.Furthermore, income taxes should become less progressive whenan optimal higher education policy is introduced.
Keywords: 330